Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1111/j.1559-1816.1994.tb01573.x
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Attitudes Toward New Immigrant Groups1

Abstract: People often receive information about new immigrant groups prior to any direct contact with group members. However, it is not clear how this information shapes attitudes toward the groups. To explore this issue, 204 subjects were told about an unknown immigrant group that was presented as high or low in personal relevance. Subjects were then given positive or negative consensus information about the emotions that group members elicit from others, group members' personality traits, and group members' values. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 20 publications
0
33
0
3
Order By: Relevance
“…Consistent with past research (e.g., Esses et al, 1993;Maio et al, 1994;Stangor et al, 1991), we measured attitudes using a scale that asked participants to rate their overall favorability toward the target group. Unlike past research, however, we could not use the ''thermometer'' measure of participants' favorability because we had already used this measure in the ''first survey,'' and we did not want to use a measure that appeared similar to the measure in the ''first survey.''…”
Section: Dependent Measuresmentioning
confidence: 83%
See 1 more Smart Citation
“…Consistent with past research (e.g., Esses et al, 1993;Maio et al, 1994;Stangor et al, 1991), we measured attitudes using a scale that asked participants to rate their overall favorability toward the target group. Unlike past research, however, we could not use the ''thermometer'' measure of participants' favorability because we had already used this measure in the ''first survey,'' and we did not want to use a measure that appeared similar to the measure in the ''first survey.''…”
Section: Dependent Measuresmentioning
confidence: 83%
“…For example, during the 1980s, newspapers in Canada published several hundred articles about the Sikh people, who were immigrating in large numbers to Canada (Maio, Esses, & Bell, 1994). Previous research has found that information about an immigrant group can affect people's attitudes toward the group and that these attitudes, once formed, predict behavioral intentions toward the group, including the endorsement of relevant immigration policies (Maio et al, 1994). Consequently, it is important to determine whether these effects are moderated by social psychological variables, such as attitude ambivalence.…”
Section: Attitude Ambivalence and The Processing Of Information Aboutmentioning
confidence: 99%
“…Moreover, a high degree of entrepreneurial activity indicates that pro-entrepreneurship attitudes prevail in a region. Students are more likely to form positive attitudes towards entrepreneurship in regions where positive information is readily accessible (Maio, Esses, and Bell 1994).…”
mentioning
confidence: 99%
“…All it takes, according to Whittenbrink (2004), is the attainment of knowledge as it is perpetuated in the social environment. Similar research has demonstrated that stereotypes and prejudice can be developed about groups with which the individual has had very little or even no direct contact (Maio, Esses, & Bell, 1994). Thus, it appears these more modern views have helped to -demystify an otherwise troublesome concept like prejudice by placing it squarely within the purview of ordinary cognition‖ (Banaji, Nosek, & Greenwald, 2004, p. 280).…”
Section: )mentioning
confidence: 93%